Mismatch Repair Deficiency and Microsatellite Instability - Sandra Schöniger; Josef Rüschoff (Encyclopedia, 2022)
Mismatch repair deficiency (MMRd) is caused by the biallelic inactivation of an MMR gene, which can be attributed either to an inherited or an acquired pathway. MMRd is characterized by the inability of cells to repair spontaneous mutations in microsatellites that occur during replication. Microsatellites are repetitive nucleotide sequences composed of one to six base pairs. Mutations in microsatellites lead to deletions or insertions of sequence units that are designated as microsatellite instability (MSI). MMRd is diagnosed by immunochemistry and is characterized by loss of nuclear immunostaining for at least one of the four MMR proteins that are routinely examined, i.e., MSH2, MSH6, MLH1 and PMS2. Available tests for MSI are PCR and next generation sequencing. MMRd and MSI predispose to tumor initiation and progression, increase tumor mutational burden as well as tumor immunogenicity, facilitate the activation of the programmed cell death protein 1/programmed cell death ligand 1 (PD-1/PD-L1) immune checkpoint pathway and serve as prognostic and predictive biomarkers in solid tumors.